Strategi Agensi ‘Bencuan’ Mengatasi Permasalahan Tutupnya Tiktok Shop dan Beralih ke Shopee - Siti Nur Afina; Selfiana Khoirunnisa; Winarsih Winarsih; Nur Hamidah; Jamiati.K.N (Institut Nalanda, 2024)
Since the outbreak of Covid-19, many employment agencies have been going live on the TikTok Shop app. However, the Government recently decided to remove this feature for one reason or another. This news has a considerable impact on TikTok Shop employment agencies, who are quite restless because they will lose a wide market reach, although the removal of TikTok Shop is a good intention to improve the e-commerce ecosystem in the country. The research uses descriptive qualitative methods with grounded theory facilitating a deeper understanding of the phenomenon under study through systematic data collection and analysis. The location of this survey was conducted at Grand Mall Serpong Tangerang on October 24, 2023. Research observations were made by interviewing the manager of the 'Bencuan' agency itself and the interview was based on grounded theory. The results of the closure of TikTok Shop in Indonesia have a huge impact on online merchants and agencies that rely on the Yellow Basket feature of Tiktok Shop. 'Bencuan' agency is not desperate or lost and continues their normal daily operations. It's just that the transaction system has changed slightly, they used to use Tiktok Shop for sales transactions, but now they are switching to other platforms such as Shopee and Instagram, because their license to operate in Indonesia is still valid.